A STRATEGY FOR MANAGING A PATIENT WITH ATRIAL FIBRILLATION TO REDUCE THE RISK OF THROMBOEMBOLIC COMPLICATIONS - L. I. Kudryavtseva; E. V. Filippov («REMEDIUM GROUP» Ltd., 2019)
Over the past 20 years, the burden of atrial fibrillation (AF) has increased. AF is associated with increased risk of death, ischemic stroke and disability, hospitalization rates, and reduced quality of life. Treatment for this pathology is based on the correction of risk factors, underlying disease and anticoagulant therapy. The review considers strategies to minimize the risk of complications during oral anticoagulant therapy.